Optimal Reconfiguration of Radial Distribution Systems to Maximize Loadability - Venkatesh, B.; Ranjan, R.; Gooi, H.B. (2004)
This paper presents a new method for optimal reconfiguration of radial distribution systems (RDS). Optimal reconfiguration involves selection of the best set of branches to be opened, one each from each loop, such that the resulting RDS has the desired performance. Amongst the several performance criteria considered for optimal network reconfiguration, maximizing loadability is an important one. Owing to the discrete nature of the solution space, a fuzzy adaptation of the evolutionary programming algorithm for optimal reconfiguration of RDS to maximize loadability is proposed in this paper. This method maximizes a fuzzy index developed using a maximum loadability index. A 33-bus RDS is optimally reconfigured by the proposed method and the results are presented.